Synthesis of D-manno-heptulose via a cascade aldol/hemiketalization reaction - Chen, Yan; Wang, Xiaoman; Wang, Junchang; Yang, You (Beilstein Journal of Organic Chemistry, 2017)
A [4 + 3] synthesis of D-manno-heptulose is described. The cascade aldol/hemiketalization reaction of a C4 aldehyde with a C3 ketone provides the differentially protected ketoheptose building block, which can be further reacted to furnish target D-manno-heptulose.
Keywords: aldol reaction; cascade reaction; D-manno-heptulose; higher-carbon sugar; ketoheptose